PENDIDIKAN ISLAM DI YAMAN - Rahmat Shodiqin (EDUCATIONAL JOURNAL : General and Specific Research, 2021)
The education system that manages education in Yemen has different Ministries at different levels. General education is under the auspices of the Ministry of Education, vocational schools and colleges are managed by the Ministry of Education and Vocational Technical Training (MoTEVT). Higher Education is regulated by the Ministry of Higher Education and Scientific Research (MoHESR). There is also a small private sector which accounts for 2% of primary and secondary and 15% respectively.